Highly complex respiratory changes in calf - Souza, Rodrigo Malzoni de; Batista, Camila Freitas; Santos, Kamila Reis; Gomes, Renata Caminha; Bertagnon, Heloisa Godoi; Libera, Alice Maria Melville Paiva Della (Brazilian Journal of Veterinary Research and Animal Science, 2018)
The bronchopneumonia of calves represents a risk to national supply chain because it is an ecopathy and weakens the more intensive production systems. It is characterized by inflammatory changes in the bronchi, bronchioles, lung parenchyma, and pleura. It is a disease of multifactorial traits called Bovine Respiratory Disease (BRD). The association of infectious agents with host defense and management to which the animal is subjected leads to the emergence of major clinical manifestations of the disease. The clinical evolution of BRD can also have serious secondary changes such as pulmonary edema, sepsis, and pulmonary hypertension, or even be consequent to the involvement of other structures, such as in cases of myocarditis leading to congestive heart failure. Although this report refers to a non-experimental framework, the circumstances that caused the calf to be subjected to a protocol-specific respiratory assessment involving non-routine reviews has made it possible to associate circulatory and respiratory conditions, rarely considered in ruminant clinic. The focus of this report was pulmonary edema. Modern clinical vision requires of the veterinarian work with cost-benefit relation, so that the more accurate and the earlier the clinical diagnosis the less expensive the treatment.